Cyclic electron flow provides acclimatory plasticity for the photosynthetic machinery under various environmental conditions and developmental stages - Suorsa, Marjaana (Frontiers in Plant Science, 2015)
Photosynthetic electron flow operates in two modes, linear and cyclic. In cyclic electron flow (CEF), electrons are recycled around photosystem I. As a result, a transthylakoid proton gradient (ΔpH) is generated, leading to the production of ATP without concomitant production of NADPH, thus increasing the ATP/NADPH ratio within the chloroplast. At least two routes for CEF exist: a PGR5-PGRL1–and a chloroplast NDH-like complex mediated pathway. This review focuses on recent findings concerning the characteristics of both CEF routes in higher plants, with special emphasis paid on the crucial role of CEF in under challenging environmental conditions and developmental stages.